Інтродукція рослин як метод збереження фітогенофонду тропічних флор ex situ: досягнення та перспективи - Buyun, L.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The main results of scientific investigations of tropical and subtropical plants under glasshouse conditions of the Department of tropical and subtropical plants of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine are summarized. The perspectives of future investigations of these plants are outlined. The data on the collections are given with emphasises on the representatives of main groups.